Supervision in Alternative Punishment: Origin, Fertilization and Resistances - Murillo, Consuelo (2021)
Nowadays we can find in common law and civil law legal systems noncustodial criminal sanctions with an intervention in the life of the offender that takes the form of supervision. In this paper, it is argued that these elements of intervention were present into alternative penalties from its inception in the common law system, which later fertilized civil law jurisdictions, that had alternative penalties without supervision. To do so, the origin and evolution of alternative penalties in both groups of jurisdictions are studied. The introduction of supervision in the civil law system in the 1960s and a second moment of fertilization or transfer in the 1990s are also taken into account, considering the broader legal and cultural processes to explain these developments and the main resistance to these changes.